VD_FINDINFO AI 101/12 - 356/2012 vom 23. Oktober 2012 - VD Tribunal cantonal (2012)
RENTE D'INVALIDITÉ, REFUS D'ENTRER EN MATIÈRE SUR CERTAINS GRIEFS, NOUVELLE DEMANDE | 69 al. 1bis LAI, 17 LPGA, 61 let. g LPGA, 87 al. 2 RAI, 87 al. 3 RAI, 82 LPA-VD